Beyond evaluative conditioning! Evidence for transfer of non-evaluative attributes - Förderer, Sabine; Unkelbach, Christian (Social psychological and personality science, 2011)
Evaluative conditioning is the valence transfer from positive or negative stimuli to initially neutral stimuli through repeated co-occurrences of those stimuli. Theoretically, it should also be possible to condition non-evaluative attributes. Three experiments show the transfer of a non-evaluative attribute: By repeatedly presenting neutral people with athletic or nonathletic people, initially neutral people became more athletic while valence was controlled for statistically and experimentally. A fourth experiment generalizes the effect to shapes and nonwords as neutral stimuli. Athleticism transfer was found on direct ratings and indirect measures (a modified affect misattribution procedure and a categorical priming task). These data broaden the applicability of conditioning as a procedure for trait acquisition with important practical implications for advertising and brand image formation.